Stature Estimation from Lower Limb Anthropometry using Linear Regression Analysis: A Study on the Malaysian Population - Abu Bakar, SN; Alias, A; Ibrahim, A; Abdullah, N; Judi, HM; Swarhib, M; Das, S; Nor, FM (Soc Editrice Univ, 2024)
Indexed by WOS/ Scopus